Healthcare providers' perspectives on integrating NCDs into primary healthcare in Thailand: a mixed method study - Titiporn Tuangratananon; Sataporn Julchoo; Mathudara Phaiyarom; Warisa Panichkriangkrai; Nareerut Pudpong; Walaiporn Patcharanarumol; Viroj Tangcharoensathien (BMC, 2021)
Abstract Background In response to an increased health burden from non-communicable diseases (NCDs), primary health care (PHC) is effective platform to support NCDs prevention and control. This study aims to assess Thailand's PHC capacity in providing NCDs services, identify enabling factors and challenges and provide policy recommendations for improvement. Methods This cross-sectional mixed-method study was conducted between October 2019 and May 2020. Two provinces, one rich and one poor, were randomly selected and then a city and rural district from each province were randomly selected. From these 4 sites in the 2 provinces, all 56 PHC centres responded to a self-administrative questionnaire survey on their capacities and practices related to NCDs. A total of 79 participants from Provincial and District Health Offices, provincial and district hospitals, and PHC centres who are involved with NCDs participated in focus group discussions or in-depth interviews. Results Strong health infrastructure, competent staff (however not with increased workload), essential medicines and secured budget boost PHC capacity to address NCDs prevention, control, case management, referral and rehabilitation. Community engagement through village health volunteers improves NCDs awareness, supports enrolment in screening and raises adherence to interventions. Village health volunteers, the crucial link between the health system and the community, are key in supporting health promotion and NCDs prevention and control. Collaboration between provincial and district hospitals in providing resources and technical support enhance the capacity of PHC centres to provide NCDs services. However, inconsistent national policy directions and uncertainty related to key performance indicators hamper progress in NCDs management at the operational level. The dynamic of urbanization and socialization, especially living in obesogenic environments, is one of the greatest challenges for dealing with NCDs. Conclusion PHC centres play a vital role in NCDs prevention and control. Adequate human and financial resources and policy guidance are required to improve PHC performance in managing NCDs. Implementing best buy measures at national level provides synergies for NCDS control at PHC level.